2016
DOI: 10.1093/bja/aew128
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of difficult videolaryngoscopy with GlideScope® or C-MAC® with D-blade: secondary analysis from a large comparative videolaryngoscopy trial

Abstract: This secondary analysis of an existing data set indicates four covariates associated with difficult acute-angle videolaryngoscopy, of which patient position and provider level are modifiable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 21 publications
3
49
1
1
Order By: Relevance
“…If videolaryngoscopy fails, one should follow the OAA/DAS guidelines, and attempt the use of a supraglottic airway device. Difficult videolaryngoscopy is not uncommon, occurring in over 25% of patients with anticipated difficult airway , but true failure appears to be rare. Difficulty should be anticipated in patients with small mouth opening, altered neck anatomy, and in those with an airway mass or history of neck irradiation, although these predictors are not specific for videolaryngoscopy .…”
Section: The Case For Videolaryngoscopes In Obstetric Anaesthesiamentioning
confidence: 99%
“…If videolaryngoscopy fails, one should follow the OAA/DAS guidelines, and attempt the use of a supraglottic airway device. Difficult videolaryngoscopy is not uncommon, occurring in over 25% of patients with anticipated difficult airway , but true failure appears to be rare. Difficulty should be anticipated in patients with small mouth opening, altered neck anatomy, and in those with an airway mass or history of neck irradiation, although these predictors are not specific for videolaryngoscopy .…”
Section: The Case For Videolaryngoscopes In Obstetric Anaesthesiamentioning
confidence: 99%
“…However, time itself should not be the determining factor in cases where awake tracheal intubation is considered the safest approach, and the alternative, tracheal intubation attempt after induction of anaesthesia in a predicted difficult airway patient may well take longer, and bears the concomitant increased risk of having to revert to emergency front-of-neck access. Mallampati classification score, were common indications for awake tracheal intubation, but evidence suggests that asleep videolaryngoscopy may often overcome this barrier [8]. One may suspect that this advancement has resulted in a reduction in the incidence of awake tracheal intubations performed, but these presumptions have not been supported by evidence to date [9].…”
Section: Why Is Awake Tracheal Intubation Underutilised?mentioning
confidence: 99%
“…This suggested that VL may not make intubation easier in severe upper airway distortion caused by malignancy or extensive oropharyngeal infection. In a secondary analysis of a data set gathered from a multicentre prospective RCT by Aziz et al (29) comparing GlideScope and Storz C-MAC D-blade VLs in 1,100 patients with anticipated difficult DL, 301 were identified as difficult VL. The multivariate logistic regression analysis showed that four predictors of difficult VL were supine sniffing position, limited mouth opening, planned otolaryngologic or cardiac surgery, and intubation by an attending anesthesiologist.…”
Section: Can Difficult or Failed Videolaryngoscopy Be Predicted?mentioning
confidence: 99%